2019
DOI: 10.1016/j.tmaid.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Middle East Respiratory Syndrome Coronavirus (MERS-CoV) infection: Extent and implications for infection control: A systematic review

Abstract: Background: The Middle East Respiratory Syndrome Coronavirus (MERS-CoV) emerged in 2012 and attracted an international attention as the virus caused multiple healthcare associated outbreaks. There are reports of the role of asymptomatic individuals in the transmission of MERS-CoV, however, the exact role is not known. Method: The MEDLINE/PubMed and Scopus databases were searched for relevant papers published till August 2018 describing asymptomatic MERS-CoV infection.Results: A total of 10 papers were retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 82 publications
2
102
0
4
Order By: Relevance
“…Importantly, MERS may be transmitted from an asymptomatic source. 73 However, super spreaders have also been reported. 74 The epidemiology and prevention of MERS in health care settings has been reviewed.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…Importantly, MERS may be transmitted from an asymptomatic source. 73 However, super spreaders have also been reported. 74 The epidemiology and prevention of MERS in health care settings has been reviewed.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…A single case of travel associated MERS-CoV infections caused the largest outbreak outside the Arabian Peninsula in South Korea [13,[15][16][17] pilgrims showed no infections [18]. There had been no asymptomatic MERS-CoV cases among travelers despite a high proportion in nontravelers [19]. A recent study included confirmed cases who were admitted to this hospital in 2014-2015 and found independent predictors of survival as younger age, not being transferred to the ICU and not receiving renal replacement therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of coronaviruses infections with high impact in public health began in 2002-2003 with the SARS outbreak [12,13] and in 2012, MERS-CoV, another highly-pathogenic coronavirus which still circulates in the Middle East and causes severe respiratory disease [14,15] was reported.…”
Section: Introductionmentioning
confidence: 99%